Finger vein recognition system for authentication of patient data in hospital - BETHANNEY JANNEY.J,; SINDU DIVAKARAN,; G.UMASHANKAR, (International Journal of Pharma and Bio Sciences, 2017)
Finger vein recognition is considered as one of the most confidential biometric which is based on the images of human finger vein patterns below the skin’s surface. Finger vein recognition system has several important features that set it distant from other forms of biometrics as highly protected and convenient means of personal authentication. In this paper, a finger-vein recognition system is proposed for database authentication in hospitals. The proposed system is applied on an embedded platform and executed with a novel finger-vein matching algorithm. The different components in finger vein recognition system includes: image acquisition, finger vein matching module, controller board and communication unit. The image acquisition unit was used to collect finger-vein images. The finger vein matching module directly gives the data of finger vein and will be analysed using discrete wavelet transform (DWT) in MATLAB. Matching the finger vein image with the database image is the main stage to verify the person’s authentication to access the patient details. The Controller board consists of Microcontroller chip,non- invasive glucose sensor, spirometer, pulse sensor and communication port was used to execute the finger-vein matching algorithm and communicate with the peripheral device. The communication unit was used to display recognition results and the sensor values if the finger vein image is matched. Since this unit is serial communication supported it can easily incorporate into any device or micro controller. Here, the person’s data will be compared with the details of the person’s previous data base with the MATLAB Software program.